Membangun Integritas dan Moralitas: Fondasi Kepemimpinan Kristen Menghadapi Era Post-Truth - Purwonugroho, Daniel Pesah (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2024)
Post-truth is a phenomenon of subjective truth circulating within society at large, driven by technological advancements. Information disseminated widely in society often lacks prior validation. Truth in this post-truth era aligns with individual preferences without undergoing validation. Christian leaders bear a significant responsibility amidst the Christian community in this post-truth era. Integrity and morality are essential attributes for Christian leaders to navigate the post-truth era. The integrity and morality of Christian leaders should be founded upon the Biblical Word of God. Without integrity and morality, Christian leaders will struggle to guide the Christian community through this post-truth era. Christian leaders need to shine a light for the Christian community amidst this post-truth era. Through descriptive qualitative methodology, it can be concluded that integrity and morality form the foundation for Christian leaders to guide the Christian community through the post-truth era. Moral and integrity-driven leaders will instill similar moral values and integrity within the Christian community, enabling them to shine amidst the post-truth era.AbstrakPost-truth adalah fenomena kebenaran yang tidak objektif yang beredar di masyarakat luas. Post-truth terjadi akibat dari kecanggihan teknologi. Informasi yang beredar luas di masyarakat tidak mengalami validasi terlebih dahulu. Kebenaran di dalam era post-truth ini adalah kebenaran yang sesuai dengan selera individu tanpa mengalami validasi. Pemimpin Kristen memiliki tanggung jawab yang besar untuk berada di tengah-tengah umat Kristen di era post-truth ini. Integritas dan moralitas adalah hal yang harus dimiliki oleh pemimpin Kristen dalam menghadapi era post-truth. Integritas dan moralitas pemimpin Kristen harus dibangun berdasarkan Alkitab Firman Allah. Tanpa integritas dan moralitas, pemimpin Kristen tidak akan berhasil membawa umat Kristen bertahan di dalam era post-truth ini. Pemimpin Kristen perlu menjadi terang bagi umat Kristen di tengah era post-truth ini. Dengan menggunakan metode kualitatif deskriptif, dapat disimpulkan bahwa integritas dan moralitas adalah dasar pemimpin Kristen membangun umat Kristen menghadapi era post-truth. Pemimpin yang bermoral dan berintegritas akan membawa umat Kristen memiliki moral dan integritas yang sama sehingga umat Kristen dapat menjadi terang di tengah era post-truth.